Peningkatan Kekuatan Jejaring Wirausaha dan E-Marketing UMKM di Banten dalam menghadapi dampak Pandemic Covid-19 - Liza Mumtazah Damarwulan; Agus David Ramdansyah; Lutfi Lutfi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to explore the economic impact, especially UMKM players in Banten on the spread of covid-19, and to identify the strength of entrepreneurial networks and the use of e-marketing by UMKM in Banten during the covid-19 pandemic. The method used in this study was analyzed by sampling using a questionnaire as a data collection tool. This questionnaire includes closed questions, measured on a nominal scale. The collected data were analyzed using the AMOS Statistical Package for the Social Sciences (SPSS) software. The results showed that there had been a decline in the marketing performance of UMKM due to the impact of the Covid-19 pandemic. And it is proven that the quality of entrepreneurial networks and e-marketing can improve the marketing performance of UMKM. From this research, a model for strengthening UMKM in dealing with the impact of the Covid-19 pandemic is obtained by strengthening entrepreneurial networks and the use of e-marketing, so that UMKM in Banten in particular and UMKM in Indonesia in general, do not fall into business collapse caused by the spread of Covid-19. The conclusion of this study is expected to contribute to the development of management science, especially marketing, entrepreneurship and the development of UMKM in dealing with the impact of the Covid-19 pandemic.